Pentahelix Collaboration Management in Natural Disaster Mitigation in West Sulawesi Province - Fadlan, ‎; Ibrahim, Muhammad Akmal; Yunus, Muhammad; Susanti, Gita (KnE Social Sciences, 2025)
Prevention and management of natural disasters cannot be done by one party alone, it requires the participation of all parties. Indonesian society needs to work together to collaborate with each other. This concept is called pentahelix or multi-stakeholder collaboration. Pentahelix combines government, community, media, academia, and business as an effort to address problems and develop programs by involving crosssectors to share roles. To achieve this goal, policies and frameworks are needed that involve all parties in building a disaster-safe culture in West Sulawesi Province. The purpose of this research is to examine existing collaboration in disaster mitigation management in West Sulawesi Province by considering how elements of the disaster Pentahelix are involved. The pentahelix collaboration theory, according to Schottle, Haghsheno, and Gehbauer, divides several factors that influence collaboration into communication, commitment, and information exchange. This research used a descriptive qualitative approach and collected data through interviews, observations, and document reviews. The researcher conducted direct interviews with 10 people who were considered to be able to provide information about the implementation of pentahelix collaboration. The informants in this study represent each element of pentahelix, namely government, business, academia, community, and media.